THE MODERN TENDENCIES OF PROFESSIONAL PSYSICAL TRAINING INDIVIDUAL DEVELOPMENT - Aleksandr E. Burov; Sergey A. Polievsky (Sport Scientific And Practical Aspects, 2025)
Now days in new political, economic, social conditions in the frame of modern concept of professional education modernization, the development of scientific-methodic bases of professional physical training continues in a number of new directions. The most actual direction in the development of professional physical culture of individual is the preventive-corrective one, that learns the process influence of physical exercises of applied directivity on the correction of psychophysical state of secondary school pupils and the ones of professional institutions of different levels. In this work defined tasks of the preventive and erection trend of preventive-erection professional physical training.